Derecho procesal civil: Apuntes y reflexiones contemporáneas para una pedagogía prospectiva del derecho - Camacho Celis, Mireya (Corporación Universitaria Americana, 2022)
The book of Procedural Law that was made exclusive as a learning tool for law students; makes each chapter topics of interest in the knowledge of Procedural Law and its new changes that occurred from the year 2012 with Law 1564, collecting in it, the great experiences that occurred with the law 1395 of 2010; so much so that while this law was seen as a decongestion tool in different areas of law. In civil matters, important advances were achieved in the solutions of civil conflicts; at the same time with it the system of hearings was put into practice, which, although they were not directed under the orality, as it brings with it the General Code of Process, in its practice led to expose, all the actions of the judge as director of the process in a much faster way by the simplification of the procedure.